Penerapan Orientasi Komposit Serat Karbon Pada Poros Kemudi Sepeda Motor Menggunakan Metode Vacuum Infusion Terhadap Kekuatan Puntir - Tyo Echa Feriandra; Firman Yasa Utama (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
A motorcycle steering shaft is subjected to torsional loads during vehicle steering; therefore, it requires a lightweight material with adequate mechanical strength. This study aimed to analyze the effect of carbon fiber orientation on the torsional strength of hollow cylindrical composite specimens fabricated using the vacuum infusion method. The specimens were manufactured from 3K 240 gsm twill carbon fiber and epoxy resin with 11 layers and fiber orientation variations of 0°, 45°, and 90°. The specimen geometry was based on a 1:2 scale model of the Honda Vario 125 steering shaft, with an outer diameter of 16.5 mm, an inner diameter of 11 mm, and a total length of 200 mm. Static torsion testing was conducted, and the experimental data were processed to determine the maximum torque, maximum shear stress, and shear modulus. The results showed that the 45° fiber orientation provided the best torsional strength, with an average maximum torque of 35.31 N·m and an average maximum shear stress of 49.89 MPa. Therefore, the 45° fiber orientation produced the highest maximum torsional strength among the tested orientation variations under laboratory conditions.